Peranan Remaja Masjid Al-Makmur dalam Meningkatkan Kualitas Shalat Berjamaah - Ilham Hidayatullah; Qurrata Akyuni; Muhammad Syarif (2021)
One of the instruments that must play a role in the implementation of the five daily prayers in congregation is the mosque administrator and also the youth of the mosque. Currently, the youth of the Al-Makmur Sibreh Mosque, Suka Makmur District, Aceh Besar District have seen the taste of reviving the mosque. The study examines the work program of mosque youth, the challenges faced and the efforts made by Al-Makmur Sibreh mosque youth in improving the quality of congregational prayers. This research is a qualitative study with a descriptive approach, data collection methods with observation, interviews and documentation techniques. This research was carried out in Suka Makmur District, Aceh Besar District, especially for Al-Makmur Sibreh mosque youth in improving the quality of congregational prayers, making direct observations related to their role and participation in mosque youth organizations. This survey descriptive research is a form of design with the aim of collecting real conditions in the field and designing about individuals (expressing opinions or responses from various parties to the problems collected). Data collection uses observation, interview and documentation collection techniques. Al-Makmur Mosque's youth work program in improving the quality of congregational prayers by carrying out various activities, namely: making regular recitations of the taklim assembly, basic recitations of the Al-Qur'an Education Park (TPA), holding religious recitations or lectures, Commemoration Days Great Islam (PHBI), calligraphy training and Friday clean.